Development of scalable video compression algorithm - Khalifa, Othman Omran; Issa, Sinzobakwira; Abomhara, Mohamed (IIUM Press, 2011)
The technology based on scalable video coding appears as a new phenomenon. The use of internet needs a huge bandwidth and possesses extreme requirements in terms of jitter, latency and loss experiences by viewers. It is very crucial to have the idea of monochrome digital video data sequence which is a set of individual pictures called frames. This frame needs to be considered as a light intensity of two dimensions, x and y, where x and y denote spatial coordinates. It is proportional to the brightness of the frame or the gray level at the point for monochrome. The normal standard speed at which these frames are displayed is 30 frames per second. This representation is called canonical representative. However. canonical representation has negative impact because it needs very huge amounts of memory. Therefore, video needs to be compressed considerably for efficient storage and sharing over the web [1].